2014
DOI: 10.1152/jn.00386.2014
|View full text |Cite
|
Sign up to set email alerts
|

The power of the mind: the cortex as a critical determinant of muscle strength/weakness

Abstract: We tested the hypothesis that the nervous system, and the cortex in particular, is a critical determinant of muscle strength/weakness and that a high level of corticospinal inhibition is an important neurophysiological factor regulating force generation. A group of healthy individuals underwent 4 wk of wrist-hand immobilization to induce weakness. Another group also underwent 4 wk of immobilization, but they also performed mental imagery of strong muscle contractions 5 days/wk. Mental imagery has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 52 publications
0
43
0
1
Order By: Relevance
“…Nevertheless, in humans, it has been shown that the M1 is a critical determinant of muscle strength (Kidgell & Pearce, ; Goodwill et al ., ; Weier et al ., ). To further support the role of the M1 and the corticospinal pathway in muscle strength, several experiments that have used a model of immobilisation have reported an increase in cortical silent period duration and a reduction in muscle strength (Clark et al ., ); however, motor training seems to attenuate the prolongation of the cortical silent period (Clark et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, in humans, it has been shown that the M1 is a critical determinant of muscle strength (Kidgell & Pearce, ; Goodwill et al ., ; Weier et al ., ). To further support the role of the M1 and the corticospinal pathway in muscle strength, several experiments that have used a model of immobilisation have reported an increase in cortical silent period duration and a reduction in muscle strength (Clark et al ., ); however, motor training seems to attenuate the prolongation of the cortical silent period (Clark et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is therefore not surprising that impairment of the NMJ, in many cases, leads to reduced muscle mass and function in both vertebrates and invertebrates (Augustin and Partridge, 2009;Tintignac et al, 2015). In addition to motor unit elimination (Piasecki et al, 2016), reduced motor axon conduction velocity (Metter et al, 1998), diminished motor cortex excitability (Clark et al, 2014;Oliviero et al, 2006), and modified activity of muscle-intrinsic factors (Proctor et al, 1998), NMJ dysfunction is strongly correlated with decreased skeletal muscle size and strength under both healthy and pathological conditions (Pratt et al, 2015). For example, recent studies suggested that the malfunction of the NMJ plays a causative role in the onset of sarcopenia (Butikofer et al, 2011), and proposed NMJ stabilisation as a way to delay its progression (Mori et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] iii) Alterations in sensory perception and cortical representation: It has been documented that prolonged bed rest, chronic LBP related MF atrophy, and persistent nociception all may lead to altered sensory perception as well as cortical misrepresentation. [10][11] Conflict between motor output and sensory feedback in the backdrop of disrupted proprioceptive representation may intrinsically heighten the activity of the pain network in absence of actual tissue damage. 10 Thus, muscle strength may be reduced with neurogenic pain associated with chronic LBP even with motor 'intention'.…”
Section: (B) Muscle Function Changes Associated With Lbpmentioning
confidence: 99%